2015
DOI: 10.5539/jel.v4n1p60
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Education Reform in Urban Educator Preparation Programs

Abstract: The majority of teachers in the United States are of a different race, ethnicity, class, gender, and linguistic dominance from that of their students. Teachers are specifically challenged by a variety of racial and ethnic issues as they enter their classrooms. This paper discusses the importance of educator preparation programs devoting attention to reforming preparation programs to include high-need clinical experiences for practicing teacher candidates. To better meet the needs of the nation's future student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…There is a current worldwide consensus that teacher preparation programs and education are in desperate need for changes and improvements if a country wants to meet the demands and challenges of 21st century (Darling-Hammond, 2010;Korthagen, 2010;Futrell, 2008). Although those programs differ in various levels around the globe in terms of depths of knowledge content, instruction and assessment, current studies agreed that teacher quality is one of the most significant determinant factors for students' progresses and achievements (Banks, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…There is a current worldwide consensus that teacher preparation programs and education are in desperate need for changes and improvements if a country wants to meet the demands and challenges of 21st century (Darling-Hammond, 2010;Korthagen, 2010;Futrell, 2008). Although those programs differ in various levels around the globe in terms of depths of knowledge content, instruction and assessment, current studies agreed that teacher quality is one of the most significant determinant factors for students' progresses and achievements (Banks, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Although Grant's "reverse design" pattern has now been widely used in foreign education system of primary, secondary and undergraduate schools, it's worth noticing that it's hardly reported that on how to improve Chinese higher vocational education curriculum system with the help of "reverse design" pattern [10][11][12] . Meet the needs of talents training is a measure of the success of higher vocational education, to test whether talent cultivation mode of higher vocational education is innovative and characteristic, the first and most important thing is the design and reform of talents training mode and talents scheme.…”
Section: Necessities Of Reformmentioning
confidence: 99%
“…As such, pre-service teachers might enter the class lacking the skills necessary to meet the needs of diverse student learners; clinical and field experiences might serve as a conduit for connecting theory and application. Ultimately, there exists a perceivable gap between the practical aspects and the theoretical foundations of effective teacher preparation (Banks, 2015;Valenzuela, 2017).…”
Section: Introductionmentioning
confidence: 99%